A COMPARATIVE STUDY OF RELIGIONS - Mugambi, J. N. Kanyua (University of Nairobi Press, 2010)
This books is the result of concerted teamwork among the academia staff of the Department of Religious Studies, University of Nairobi between 1986 and 1990. The Project was prompted by the necessity to produce relevant and comprehensive textbooks for the undergraduate degree programme. The book has remained in demand, confirming the relevance and quality of its content covering the whole range of major religions of the world with extensive geographical and historical scope. It includes a specific section on African Religion, thus placing the African Religious Heritage within the mainstream of the comparative study of the world's religions.